2022
DOI: 10.7554/elife.82244
|View full text |Cite
|
Sign up to set email alerts
|

SRSF6 balances mitochondrial-driven innate immune outcomes through alternative splicing of BAX

Abstract: To mount a protective response to infection while preventing hyperinflammation, gene expression in innate immune cells must be tightly regulated. Despite the importance of pre-mRNA splicing in shaping the proteome, its role in balancing immune outcomes remains understudied. Transcriptomic analysis of murine macrophage cell lines identified Serine/Arginine Rich Splicing factor 6 (SRSF6) as a gatekeeper of mitochondrial homeostasis. SRSF6-dependent orchestration of mitochondrial health is directed in large part … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…[ 31 ] A recent study reported that SRSF6 deletion promotes the retention of BAX intron 1 to generate BAX‐k, an isoform that sensitizes macrophages to undergo apoptosis. [ 32 ] In the present study, we demonstrated that PQBP1 knockdown promoted exon 2 inclusion to generate BAX‐L. In contrast, ectopic expression of PQBP1 promoted BAX exon 2 skipping and led to a premature termination codon and to a truncated isoform that underwent nonsense‐mediated decay.…”
Section: Discussionmentioning
confidence: 55%
“…[ 31 ] A recent study reported that SRSF6 deletion promotes the retention of BAX intron 1 to generate BAX‐k, an isoform that sensitizes macrophages to undergo apoptosis. [ 32 ] In the present study, we demonstrated that PQBP1 knockdown promoted exon 2 inclusion to generate BAX‐L. In contrast, ectopic expression of PQBP1 promoted BAX exon 2 skipping and led to a premature termination codon and to a truncated isoform that underwent nonsense‐mediated decay.…”
Section: Discussionmentioning
confidence: 55%
“…To pinpoint where in the type I IFN signaling response SRSF7 acts, we treated Srsf7 KD or SCR RAW MΦs with LPS and measured secretion of IFN-β/α over a 6 h time course via an ISRE-luciferase reporter cell line. 11 , 42 Srsf7 KD MΦs produced significantly less IFN-β/α compared to SCR controls at all time points measured ( Figure 3A ). We next asked if impaired ISG expression in Srsf7 KD MΦs could be rescued if Srsf7 KD and SCR control cells received equal amounts of recombinant IFN-β.…”
Section: Resultsmentioning
confidence: 94%
“… 8 10 We recently implicated SRSF6 in maintaining mitochondrial homeostasis and antiviral immunity in MΦs by controlling AS of the pro-apoptotic factor BAX. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Upon pathogen detection, macrophages modulate SRSF6 expression to control the release of immunogenic mtDNA and adjust the threshold for initiating programmed cell death. 140 QKI-5 plays a role in macrophage differentiation. 141 During the progression of atherosclerosis, QKI-5 serves as a dynamic regulator of ASE and expression profiles, driving monocyte activation, adhesion, and differentiation into macrophages, thereby contributing to disease progression.…”
Section: Alternative Splicing and Related Rbps In The Reproductive Sy...mentioning
confidence: 99%